Tupai pada Karya Tapestri - Andaresta, Rina; Jupriani, Jupriani (Lembaga Yasin AlSys, 2023)
The purpose of this final work is to visualize the life of a squirrel into a tapesrtri work using the techniques available on tapestri. The author makes squirrels as objects in tapestri works because of the visual form of the cute and unique squirrel character, from his gestures and adorable behavior. The author was inspired to visualize the shape of a squirrel into the form of a tapestri work and make it a wall decoration work. The method of creation in this final work is carried out in stages, starting from the preparation stage by looking for ideas by making observations, elaboration by collecting various data, synthesis of establishing ideas, the stage of realization of the concept of making tapestri artwork, and the stage of completion by conducting joint exhibitions. Seven tapestri works with a size of 60 cm x 50 cm with the main media wool yarn based on the theme